2017
DOI: 10.1177/1362480616684194
|View full text |Cite
|
Sign up to set email alerts
|

Seeing crime, feeling crime: Visual evidence, emotions, and the prosecution of domestic violence

Abstract: Changes in prosecutorial strategies vis-a-vis domestic violence introduced new models of investigation that privilege images of victims. Drawing on case law, we argue these visual artefacts of victims’ injuries as well as their videotaped sworn statements describing their assaults constitute what Haggerty and Ericson call a ‘data double’, a virtual doppleganger who is meant to stand, often antagonistically in the stead of the flesh and blood victim. We further suggest, following theorizing on the emotional imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…• Potential evidence of perceived injustice [30]. • A frame for sharing perceived injustice events in context [43].…”
Section: Video Activismmentioning
confidence: 99%
See 2 more Smart Citations
“…• Potential evidence of perceived injustice [30]. • A frame for sharing perceived injustice events in context [43].…”
Section: Video Activismmentioning
confidence: 99%
“…This means that images have a greater impact than text or audio alone and the picture sticks with the viewer for longer periods of time. Videos can also combine multiple sources of media and images into powerful collages, as the "victim's data double becomes more human than human" [30]. Framing is also critical because the filmmaker's perspective colors their perception and representation of events.…”
Section: Video Activismmentioning
confidence: 99%
See 1 more Smart Citation
“…Around the world, it is customary to use visual ads in campaigns (Wakefi eld et al 2010) to direct people's att ention to specifi c problems (Kilbourne 1999) including DV (Borzekowski and Poussaint 1999;Hill 2000). A growing body of research in criminology and socio-legal studies has also examined, for example, how, in the context of the courtroom, visual aids can convey the truth about domestic violence against women (Biber 2006;Moore and Singh 2017). In advertisement, it is believed that images can communicate the same message to large audiences repeatedly over time (Wakefi eld et al 2010(Wakefi eld et al : 1262.…”
Section: Talking Images and Anti-violence Signs In Cosmopolitan Spacesmentioning
confidence: 99%
“…She stated that there are unanswered questions around several key issues: privacy and confidentiality (of both victims and suspects), access a victim has to filmed footage and the subsequent potential of footage being made public, as well as other evidentiary challenges such as security and evidentiary standards of recording. Finally, Moore and Singh (2017) observed that using VVS as evidence-in-chief during a prosecution removed the ability of victims to change or alter their accounts of victimization incidents. Their study found “the reliance on visual evidence often serves to facilitate the silencing of domestic violence victims and the further removal of their agency within the prosecution of their assaults” (p. 128).…”
mentioning
confidence: 99%